Locomotion Mode Affects the Physiological Strain during Exercise at Walk-Run Transition Speed inElderly Men - Freire, Raul; Farinatti, Paulo; Cunha, Felipe; Silva, Brenno; Monteiro, Walace (International Journal of Sports Medicine, 2017)
This study investigated cardiorespiratory responses and rating of perceived exertion (RPE) during prolonged walking and running exercise performed at the walk-run transition speed (WRTS) in untrained healthy elderly men. 20 volunteers (mean±SE, age: 68.4±1.2 yrs; height: 170.0±0.02 cm; body mass: 74.7±2.3 kg) performed the following bouts of exercise: a) maximal cardiopulmonary exercise test (CPET); b) specific protocol to detect WRTS; and c) two 30-min walking and running bouts at WRTS. Expired gases were collected during exercise bouts via the Ultima CardiO2 metabolic analyzer. Compared to walking, running at the WRTS resulted in higher oxygen uptake (>0.27 L·min−1), pulmonary ventilation (>7.7 L·min−1), carbon dioxide output (>0.23 L·min−1), heart rate (>15 beats·min−1), oxygen pulse (>0.88 15 mL·beats−1), energy expenditure (>27 kcal) and cost of oxygen transport (>43 mL·kg−1·km−1·bout−1). The increase of overall and local RPEs with exercise duration was similar across locomotion modes (P<0.001). In all participants, %HRR and %VO2R throughout walking and running bouts were around or above the gas exchange threshold. In conclusion, elderly men exhibited higher cardiorespiratory responses during 30-min bouts of running than walking at WRTS. Nevertheless, walking corresponded to relative metabolic intensities compatible with preservation or improvement of cardiorespiratory fitness and should be preferable over running at WRTS in the untrained elderly characterized by poor fitness and reduced exercise tolerance.
Keywords: walk-run transition speed; oxygen uptake reserve; heart rate reserve; perceived exertion; gas exchange threshold; exercise prescription